Empowering Farmers Through Innovation in Plant Clinic Development - Rachmawatie, Dessy (Journal of Environmental Economics and Sustainability, 2024)
This service aims to increase farmers' knowledge of how to control pests and diseases of rice plants by developing a plant clinic in Sumber Village, Trucuk District, and Klaten Regency. So that farmers have increased knowledge and capacity in dealing with the problems of controlling pests and diseases of the rice plants they manage. The community service method is counseling and direct interviews with the Association of Farmers Groups (GAPOKTAN) "Rukun Tani" at the village level. GAPOKTAN “Rukun Tani” consists of 3 farmer groups, including (1) Sumber Rejeki Farmer Group, (2) Sido Makmur Farmer Group, and (3) Margo Mulyo Farmer Group. Previously, there was a Plant Clinic in Sumber Village, but currently, the existence of the Plant Clinic is not developing, so one of the essential problems for GAPOKTAN Rukun Tani is to develop the existing Plant Clinic so that all members of the Farmer Group in Sumber Village can reuse, Trucuk District, Klaten Regency.